The Needs Analysis of Thematic Learning Model Based on Aneuk Jamee Culture Integrated with HOTS - Mardhatillah; Khairil Ansari; Abdurahman Adisaputera (Britain International of Humanities and Social Sciences (BIoHS) Journal, 2020)
The aim of this research is to analyze the needs of the development of thematic learning model based on aneuk jamee culture integrated with HOTS. The study was conducted by survey method in 9 Elementary Schools in South Aceh Regency. The research subjects were 18 classroom teachers who taught thematic learning. The object studied was the principal's response to the development of a thematic learning model based on Aneuk Jamee tribe integrated with HOTS, the tendency of teachers to apply thematic models in school learning, student reasoning, and student character. Data collected by interview, questionnaire, observation, and test. Data were analyzed descriptively. The results of the analysis show that (1) principals have not yet fostered the development of thematic models, so they support development efforts, (2) teachers have not yet developed and used thematic models, so they support and express readiness to be involved in development, (3) learning models used by teachers so far there are no indications that lead to thematic models based on Aneuk Jamee integrated with HOTS.